Peningkatan Pemahaman Nilai Hidup Sederhana Melalui Pembelajaran Kontekstual Dalam Pembelajaran Al Qur'an Dan Hadis Di MAN 1 Aceh Timur - Razali, Rahmawati (Jurnal Aktual Pendidikan Indonesia, 2023)
This research raises the issue of whether the application of contextual learning can improve student learning outcomes and student activities in the Simple Values of Life material for class XII MAN 1 East Aceh. To obtain answers to these problems, the classroom action research method was used. The subjects of this research were 28 students in class XII MAN 1 East Aceh for the 2021/2022 academic year. Research data was obtained through observation and test techniques, and analyzed by determining the average student learning outcomes, percentage of learning completeness and average student activity. The research results prove that the application of contextual learning in the material of understanding the value of a simple life in class XII MAN East Aceh can improve student learning outcomes each cycle. This can be seen from the average student learning outcomes in cycle I of 64.64 with a completion percentage of 64.29%, cycle II of 73.21 with a completion percentage of 75.00%, and cycle III of 83.21 with a completion percentage of 89. .29% so that classical learning completeness is achieved. Thus, the application of contextual learning can overcome students' learning difficulties in understanding the value of a simple life at MAN 1 East Aceh. The average level of student activity in cycle I was 3.28 in the sufficient category, in cycle II it was 3.71 in the good category, and in cycle III it was 4.36 in the good category. This shows that the application of a contextual approach in learning the Qur'an and Hadith can increase student activity and creativity.